Toleransi Antarumat Beragama di Indonesia dari Perspektif Etika Kepedulian - Yeremias Jena (Institut Teknologi Sepuluh Nopember, 2019)
Dialogue and co-existence between religious believers have been practiced quite extensively in Indonesia, especially since the New Order era. From the beginning, it did happen top-down because of the government's political strategy to create a peaceful and stable society for the success of physical development. However, in subsequent developments, the importance of changing approaches to dialogue and cooperation between religious believers was considered as an urgent matter. Therefore, the active involvement of citizens and the creation of social spaces for the interaction and encounter of citizens of different religions, ethnicities and cultures have been initiated and practiced by the government in many regions of Indonesia. Unfortunately, intolerant and exclusive attitudes among citizens still occur. By using philosophical inquiry methods to analyze various practices of interreligious dialogue in Indonesia, it was found that first, there has been a change in approach in interreligious dialogue in Indonesia. Second, it is increasingly being realized that social spaces for encounters between different citizens must continue to be expanded as a medium to combat intolerant attitudes. Third, caring ethics, especially aspects of attention, can be a moral and philosophical foundation that strengthens caring interactions between citizens in the social space that has been formed